Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages total number of cubic feet in the room should then be divided by the average number of users. Apart from the actual cubic space, other commonsense considerations should be borne in mind. For instance one ought to be more stringent where much of the room is occupied by machinery ; and one can be much less fussy where, by the nature of the process or for some other reason, there is a large intake of fresh air. In workrooms where the occupants are not moving to and fro, care should be taken to see that the benches and seats are not so arranged that one row of workers are constantly breathing in another row's faces. If they must work opposite each other with only two feet or so between them, it would save many weeks of absenteeism every year from spreading colds and flu, if there were a barrier of glass or mica between the rows. Lighting Eyes can adjust to wide variations in illumination, ranging from thousands of foot-candles* when working in bright sunlight, to half a foot-candle in a badly-lit factory, but this adjustment is a strain. Bad light, or sometimes too much light, may mean headaches, a feeling of fatigue, increased accidents, inaccuracy of work, and on this latter account anxiety on the part of the worker. The Factories Act says that every part of the factory where people have to work or pass should be properly lighted, either naturally or artificially. There are new regulations under the Factories (Standards of Lighting) Regulations 1941 (S.R. & O. 1941 No. 94), which apply to any factory where people are working more than 48 hours a week or are working on shifts. In practice these regulations mean that the lights should not cause glare, that all local lighting should be shaded, and that there should be general evenly distributed lighting. Certain measures should also be taken to prevent the formations of shadows which cause eyestrain or risk of accident. If workers have reason to suppose that the standard of lighting is inadequate or does not comply with the regulations, they should ask for figures as to what the amount of lighting is in different parts of the building. Where work is actually being done, the minimum lighting should be six foot-candles at three feet above floor level. For special processes much more light may be needed. For fine machine work 15 to 25 foot-candles is recommended, and for skilled bench work 10 to 15 foot-candles. In other parts *A foot-candle is defined as the illumination at a point 1 foot away from the flame of a standard candle. 5 21/2049